Performance of Permeable Pavement with Subsurface Micro Detention Storage as Rainwater Harvesting Device - Norazlina, Bateni; Lai, S.H.; Mohammad, Abdul Mannan; Jethro, Henry Adam; Kuryati, Kipli; Rosmina, Ahmad Bustami (SpringerNature, 2020)
In this paper, permeable pavement, which is a sustainable infrastructure, is designed with subsurface micro detention pond storage, called, StormPav. The product is designed with a cylindrical hollow space of 70% void volume and occupied about 0.19 m3 /m2 pavement area for rainwater harvesting device. The experimental investigations for application asa rainwater harvesting were conducted in the laboratory. The hydrology parameter variables examined included volume capacity at various rainfall intensities, volume parameters (water depth and applicable area) and system properties. A modelling simulation using Stormwater Management Model (SWMM) to verify laboratory results. A further simulation of a case study for various sizes of rain barrels was performed. The results showed that the product proved advantageous on a bigger space and volume of void content to provide for a rainwater harvesting system with a connected underground storage tank.